Monitoring one heart to help two: heart rate variability and resting heart rate using wearable technology in active women across the perinatal period - Shon P. Rowan; Christa L. Lilly; Elizabeth A. Claydon; Jenna Wallace; Karen Merryman (BMC, 2022)
Highlights • Continuous monitoring of heart rate variability and resting heart rate throughout the perinatal period has not been previously performed. • Prior studies have indicated heart rate variability changes per trimester. However, at 49 days prior to delivery there is a reversal of the changes not previously seen. • Most patients are not currently wearing a physiologic monitor. If further research shows significant changes in disease states, using physiologic monitors may become an important part of obstetric management.